Fundamentalisme Pendidikan Agama di Jejaring Sosial - Muhamad Tisna Nugraha (IAIN Ponorogo, 2018)
Abstract: Social Media is like two sides of the same coin; has positive and negative sides. As for a positive side, it is used to share information, technology and scientific issues as well as maintain social relationship; on the other side, it may be a means of spreading intolerant notions toward diversity. Furthermore, these notions may become exclusive fundamentalism which is anti-criticism, especially when it contains political, economic, and legal interests, and even worst, if it involves aninterpretation of religious verses. This paper is a library research based on social phenomenology approach which aims to give solution to problems of religious fundamentalism before turning into radicalism and vandalism. There are two possible solutions. Firstly, social media should provide balance information in order to avoid old orientalism prejudice; second, it should show Islam objectively; it should be according to Islamic law not western thought and culture (ghazw al-fikr wa ghazw ats-thaqafi).الملخص: يمكن تشبيه وسائل التواصل الاجتماعية بعملة ذات الوجهين، الايجابية والسلبية. من الجانب الإيجابي فتكون وسائل الإعلام الاجتماعية مكانا لمشاركة المعلومات والتكنولوجيا والمناقشة العلمية ومحلا لصلة الرحم بين مستخدميها في الفضاء السيراني. ومع ذلك، من ناحية أخرى، فقد تجعل هذه الوسائل محلا لغرس المفاهيم الدينية الّلاتسامحية. وإذا اتصل الجانب السلبي المصالحَ السياسية والاقتصاد والقانون وحتى في مجال تفسير النصوص المقدسة فإنه سيُولِد أيدوليجية